Geometric risk factor and disturbed blood flow in the genesis of atherosclerosis - Wasilewski, Jarosław; Kiljański, Tomasz; Głowacki, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Despite the fact that the classic risk factors are systemic, distribution of atherosclerotic plaques in the arteries is not random. The relationship between spatial localization of lesions and arterial geometry is well documented. Bifurcations, side branches and inner wall of vessel curvature are the risk points of plaque formation where the flow profile is no longer axially symmetrical or a complex secondary flow can develop (disturbed flow). In the pulsatile flow, departures from the laminar flow most frequently last only in the short-period of the systolic phase of a heart cycle, or are not related to the total volume of the stream. It is difficult to differentiate whether the flow is turbulent or only disturbed. Thus, the concept of the disturbed flow is broad and implies the existence of deviation from the laminar flow. The term “disturbed flow” includes the separation of the boundary layer (flow separation) which leads to the formation of secondary and retrograde flows, as well as lateral and eddy currents, oscillating flows or other not determined non-laminar flows. The paper discusses the importance of arterial geometry in the formation of disturbed flows and their role in the atherosclerotic process.